2020
DOI: 10.1186/s12885-020-07305-2
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of treatment with CHOP and EPOCH in patients with HIV associated NHL in a low resource setting

Abstract: Background: The optimal chemotherapy regimen for treating HIV associated NHL in low resource settings is unknown. We conducted a retrospective study to describe survival rates, treatment response rates and adverse events in patients with HIV associated NHL treated with CHOP and dose adjusted-EPOCH regimens at the Uganda Cancer Institute. Methods: A retrospective study of patients diagnosed with HIV and lymphoma and treated at the Uganda Cancer Institute from 2016 to 2018 was done. Results: One hundred eight pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Of these, 215 articles were excluded resulting in 154 studies that met the selection criteria. We excluded 25 studies with no usable data: 23 did not report baseline risk for mortality by BMI group, 17‐39 1 only reported a p value, 40 and another 1 mentioned data in a supplement that were not available 41 . Disagreements about the inclusion of studies occurred in 16% of the articles ( kappa = 0·67).…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 215 articles were excluded resulting in 154 studies that met the selection criteria. We excluded 25 studies with no usable data: 23 did not report baseline risk for mortality by BMI group, 17‐39 1 only reported a p value, 40 and another 1 mentioned data in a supplement that were not available 41 . Disagreements about the inclusion of studies occurred in 16% of the articles ( kappa = 0·67).…”
Section: Resultsmentioning
confidence: 99%
“…The complete response of 55% (95% CI 45%; 65%) and 2-year OS of 59% (95% CI 50%, 69%) was an improvement on a study from the Western Cape province of SA which reported a CR of 39% and 2 year OS of 40.5% [14]. Of interest a study from Uganda, which like the Western Cape study reported exclusively on the use of CHOP, showed a CR of 27% [14,39].…”
Section: Discussionmentioning
confidence: 84%
“… 10 , 22 , 29 Only in recent years, multiple hospital-based studies have shed more light on feasibility of grade- and subtype-directed treatment approaches in SSA, eg, on AIDS-related DLBCL, 30 aggressive B- and T-cell lymphoma, 20 BL, 18 and HIV-associated aggressive NHL. 31 We suggest that in case of further amendment of NCCN Harmonized Guidelines, recommendations for treatment of high- and low-grade lymphoma may be considered when further subtyping is not feasible.…”
Section: Discussionmentioning
confidence: 98%